2010
DOI: 10.2478/s11535-010-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining Beauveria bassiana and Nosema pyrausta on the mortality of Ostrinia nubilalis

Abstract: Abstract:We tested the combined effect of the fungus Beauveria bassiana and the microsporidium Nosema pyrausta on the European corn borer larvae, Ostrinia nubilalis, in the laboratory. The first instar of O. nubilalis larvae was the most sensitive to the B. bassiana infection followed by the fifth, second, third, and fourth instar (LC 50 s were 4.91, 6.67, 7.13, 9.15, and 6.51 x 10 5 conidia/ml for the first to fifth instars, respectively). Mortality of each instar increases positively with concentration of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As the baiting insect G. mellonella belongs to Lepidoptera , isolates should have potential to infect it. Several previous studies (Abdel Rahman, Barta, & Cagáň, 2010; Demír, Secil, Demirbag, & Sevim, 2012) reported similar mortality; however, it depends on used strains as well as bioassay design. Safavi et al (2012) found average mortality for 10 7 conidia in ml in the range 12%–42% and highest mortality 57% after application of 10 8 dose.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…As the baiting insect G. mellonella belongs to Lepidoptera , isolates should have potential to infect it. Several previous studies (Abdel Rahman, Barta, & Cagáň, 2010; Demír, Secil, Demirbag, & Sevim, 2012) reported similar mortality; however, it depends on used strains as well as bioassay design. Safavi et al (2012) found average mortality for 10 7 conidia in ml in the range 12%–42% and highest mortality 57% after application of 10 8 dose.…”
Section: Resultsmentioning
confidence: 89%
“…Strain was able to overgrow 70% of cadavers by mycelia and sporulate when applied in dose 10 8 conidia in ml. Higher mortality can be achieved when fungus is applied together with another biocontrol agent like Bacillus thuringiensis (Wraight & Ramos, 2005) or N. pyrausta (Abdel Rahman et al, 2010) alternatively with sub‐lethal dose of chemical insecticide (Foschi & Grassi, 1985). In comparison with mentioned studies, our results indicate that SUAa83 can be good candidate for O. nubilalis regulation and will be subjected to field testing of efficiency to O. nubilalis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the combination of Beauveria bassiana and Nosema pyrausta (Paillot) Weiser c was used in laboratory, the mortality of the European corn borer larvae, Ostrinia nubilalis, increased significantly in all instars. Relative to the B. bassiana treatment alone, the B. bassiana + N. pyrausta treatment decreased the LC50s by 42.16 %, 37.63 %, 21.60 %, 27.11 % and 33.95 % for the first to the fifth instars, respectively (Rahman et al, 2010).…”
Section: Case Studies In Generalmentioning
confidence: 92%
“…B. bassiana is the most well studied entomopathogenic fungi and has been frequently used as a commercial mycoinsecticide in the feld [5,6]. For example, B. bassiana was used to control insect pests, including Pissodes castaneus, Ostrinia nubilalis, and Rhynchophorus ferrugineus, infeld through direct spraying [7][8][9]. It is known that B. bassiana is safe to human, natural benefcial insects, and benefcial microorganisms.…”
Section: Introductionmentioning
confidence: 99%